Locally Resonant Phononic Crystals at Low frequencies Based on Porous SiC Multilayer - Mehaney, Ahmed (Sci Rep, 2019)
In this work, a one-dimensional porous silicon carbide phononic crystal (1D-PSiC PnC) sandwiched between two rubber layers is introduced to obtain low frequency band gaps for the audible frequencies. The novelty of the proposed multilayer 1D-PnCs arises from the coupling between the soft rubber, unique mechanical properties of porous SiC materials and the local resonance phenomenon. The proposed structure could be considered as a 1D acoustic Metamaterial with a size smaller than the relevant 1D-PnC structures for the same frequencies. To the best of our knowledge, it is the first time to use PSiC materials in a 1D PnC structure for the problem of low frequency phononic band gaps. Also, the porosities and thicknesses of the PSiC layers were chosen to obtain the fundamental band gaps within the bandwidth of the acoustic transducers and sound suppression devices. The transmission spectrum of acoustic waves is calculated by using the transfer matrix method (TMM). The results revealed that surprising low band gaps appeared in the transmission spectra of the 1D-PSiC PnC at the audible range, which are lower than the expected ones by Bragg’s scattering theory. The frequency at the center of the first band gap was at the value 7957 Hz, which is 118 times smaller than the relevant frequency of other 1D structures with the same thickness. A comparison between the phononic band gaps of binary and ternary 1D-PSiC PnC structures sandwiched between two rubber layers at the micro-scale was performed and discussed. Also, the band gap frequency is controlled by varying the layers porosity, number and the thickness of each layer. The simulated results are promising in many applications such as low frequency band gaps, sound suppression devices, switches and filters.